Protection of Children's Rights Through Public Policy: A Review of the Implementation of Child Protection Programs in Elementary Schools - Undang Ruslan Wahyudin; Fajar Noor Fuji Sutarjo; Asim Supriadi; Verisca Ayu Hikma (Journal of Pedagogi, 2024)
The welfare and protection of children's rights are crucial elements in sustainable community development. In this context, public policy plays a key role in ensuring that children receive adequate protection and opportunities to grow and develop properly. This paper investigates the implementation of child protection programs in primary schools as one of the concrete efforts to ensure that children's rights are safeguarded. By focusing on the policies, implementation process, and impacts of these programs in several elementary schools, this study aims to provide a comprehensive understanding of the effectiveness of such initiatives. Using a qualitative research method, data was collected through interviews, observations, and document analysis to examine how these programs are integrated into the school system and their outcomes on children's well-being. The findings reveal that while there are significant efforts and resources allocated towards child protection, there are also challenges and gaps that need to be addressed to enhance the effectiveness of these programs. The study concludes with recommendations for policymakers, educators, and community stakeholders to improve the implementation and impact of child protection initiatives, ensuring that every child enjoys a safe and supportive environment conducive to their holistic development.